The Scavenger Receptor SREC-I Cooperates with Toll-Like Receptors to Trigger Inflammatory Innate Immune Responses - Murshid, Ayesha; Borges, Thiago J.; Lang, Benjamin J.; Calderwood, Stuart K. (Frontiers in Immunology, 2016)
Scavenger receptor expressed by endothelial cell-I (SREC-I) is a class F scavenger receptor expressed by immune cells with a significant role in CD8+- and CD4+-mediated T cell immunity. This receptor can also modulate the function of toll-like receptors (TLRs), which play essential roles in innate immunity. Earlier, it was found that human monocyte/macrophage THP1 cells and bone marrow-derived macrophages from mice exhibited increased responses to polyinosine–polycytidylic acid (poly I:C, PIC) and CpG (unmethylated) DNA and enhanced production of inflammatory cytokines with overexpressed SREC-I. Our data also showed that intracellular/endocytic TLR3 and TLR9 could directly interact with SREC-I in the presence of their respective ligands. We also observed that the internalized ligand along with TLR3/TLR9 colocalized in the endosome in macrophages and THP-1 cells overexpressing these receptors. In the absence of these ligands, there was no detectable colocalization between the SREC-I and endocytic TLRs. Earlier, it was shown that SREC-I stimulated double-stranded RNA/CpGDNA-mediated TLR3/TLR9 activation of the innate immune response by triggering signaling through the NF-κB, IRF3, and MAP kinase pathways leading to transcription of cytokine genes. We also established that SREC-I can associate with plasma membrane TLRs, such as TLR2 and TLR4. We demonstrated that SREC-I–TLR4 signals more efficiently from lipid microdomain in which lipopolysaccharide (LPS) can associate with SREC-I–TLR4 complex. We also proved that SREC-I is an alternate receptor for LPS capable of internalizing the complex and for endocytic TLR ligands as well. This binding activated endocytic TLR-mediated downstream cytokine production in THP1 cells and macrophages. Finally, SREC-I could also form complexes with TLR2 and induce the release of cytokines in the presence of bacterial, viral, and fungal ligands.